Graduate registered nurses' reflections on implementing safety and quality improvement projects. Issue 5 (3rd September 2018) - Saunders, Dr. Rosemary; Arnold, Emma; Seaman, Karla; Green, Anne; Gullick, Karen
ABSTRACT: Registered nurses are required to be involved in quality improvement activities as part of delivering safe, high-quality care for patients. Graduate registered nurses often have limited knowledge and practical application of quality improvement processes and their link to clinical care. Graduate nurse programs provide ideal opportunities to embed knowledge and practice of quality standards and quality improvement processes and for graduates to utilise reflection as an important tool in learning and practice review. An innovative approach was implemented at an Australian private hospital where registered nurses in a graduate nurse program worked in groups to conduct a quality improvement project relating to one of the Australian National Safety and Quality Health Service Standards. As part of the project, reflection was used as a strategy for graduates to understand and learn from their experience. Using a descriptive qualitative approach, the reflections of 20 graduate registered nurses who conducted a quality improvement project as part of a graduate nurse program were analysed. The results showed that reflection enabled the graduate nurses to better understand their experience of implementing a quality and safety project with a team of peers, including reflecting on their own learning and also reflecting on quality improvement projects and how they can contribute to improved practices at the hospital.